1995
DOI: 10.2118/27558-pa
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Well-Test Models by Use of Higher-Order Neural Networks

Abstract: In a well test, the central objective is to "prove" the fonnation in terms of a sustainable economic flow rate. This objective is related to the characterization of the reservoir and the estimation of its parameters, like permeability and skin, by knowledge of only the input and output signals, such as pressure and flow rate, and, in certain cases, other reservoir characteristics, such as the drainage area and the distance to faults.Interpretation efforts, therefore, can be performed in two phases: (l) the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It is important to note that this study is fundamentally different to previous applications of Artificial Intelligence in the field of Pressure Transient Analysis (e.g., Al-Kaabi and Lee, 1990;Allain and Horne, 1990;Deng et al, 2000;Ershaghi et al, 1993;Kumoluyi et al, 1995;Sinha and Panda, 1996;Sung et al, 1995). These previous studies mostly focused on the automatic identification of analytical models for Pressure Transient Analysis to assist the well test interpretation, assuming that appropriate analytical models to represent real reservoirs exist.…”
Section: Manuscript Submitted To Transport In Porous Mediamentioning
confidence: 92%
“…It is important to note that this study is fundamentally different to previous applications of Artificial Intelligence in the field of Pressure Transient Analysis (e.g., Al-Kaabi and Lee, 1990;Allain and Horne, 1990;Deng et al, 2000;Ershaghi et al, 1993;Kumoluyi et al, 1995;Sinha and Panda, 1996;Sung et al, 1995). These previous studies mostly focused on the automatic identification of analytical models for Pressure Transient Analysis to assist the well test interpretation, assuming that appropriate analytical models to represent real reservoirs exist.…”
Section: Manuscript Submitted To Transport In Porous Mediamentioning
confidence: 92%
“…Although the pressure derivative data are typically used in the normalized form as input to the ANN, it has been found that normalizing poses the following problems (Kumoluyi et al, 1995;Deng and Chen, 2000):…”
Section: Methodsmentioning
confidence: 99%
“…Using the actual well test curve to train ANN is not the appropriate approach because the training sample aggregate is too large, which made it difficult to train ANN successfully. The theory pressure derivative curves were selected as the training samples in the literatures [1][2][3][4][5][6] , and the input vector of ANN was the data point series selected from the theory pressure derivative curve. Before inputting to ANN, the vectors must be normalized.…”
Section: Literatures Reviewmentioning
confidence: 99%
“…That is because the traditional normalization of data points can't efficiently unit the input vectors of actual tested curve to the same model area as its training samples. Some researchers have noticed this problem and proposed different methods 5,6 to uniform the tested curve and the training samples, but they are not the most efficient approaches. It has been demonstrated in this study that using data point series as input vectors to train ANN is not the appropriate approaches.…”
Section: Introductionmentioning
confidence: 99%